2D‐MA3Sb2I9 Back Surface Field for Efficient and Stable Perovskite Solar Cells. Issue 6 (28th April 2021) - Yuan, Haobo; Zhang, Jing; Yu, Luting; Guo, Tonghui; Zhang, Zequn; Wang, Yanyan; Shang, Minghui; Liu, Xiaohui; Hu, Ziyang; Zhu, Yuejin; Han, Liyuan
Abstract: In perovskite solar cells (PSCs), a defective perovskite (PVK) surface and cliff‐like energy offset at the interface always slow down the charge extraction; meanwhile, interface ion diffusion causes oxidation of the metal electrode, inducing device instability. Here, the in situ grown 2D‐(CH3 NH2 )3 Sb2 I9 (MA3 Sb2 I9 ) on the back surface of MAPbI3 results in a more robust interface. MA3 Sb2 I9 changes the MAPbI3 surface to p‐type and thus acts like a back surface field to drive charge extraction and suppress recombination, resulting in an obviously higher fill factor (FF) = 0.8 and power conversion efficiency (PCE) = 20.4% of SnO2 /MAPbI3 /MA3 Sb2 I9 /Spiro‐OMeTAD (2, 2′, 7, 7′‐Tetrakis[N, N‐di(4‐methoxyphenyl)amino]‐9, 9′‐spirobifluorene) PSC than the pure MAPbI3 device. More importantly, strong chemical bonding of SbI prohibits ion diffusion, largely enhancing the thermal stability and longtime stability. Here, special 2D‐MA3 Sb2 I9 constructs' robust band alignment and chemical environment at the interface are highlighted for efficient and stable PSCs. Abstract : Here, a special method of 2D‐MA3 Sb2 I9 back surface field (BSF) is highlighted for efficient and stable perovskite solar cells (PSCs). MA3 Sb2 I9 changes the MAPbI3 surface to be more p‐type and thus acts as a BSF to drive charge extraction. More importantly, strong chemical bonding of SbI prohibits ion diffusion, largely enhancing the thermal stability and long‐term stability.